Language function and knowledge construction in online discussion board forums - Alice Shanthi; Lee, Kean Wah; Denis Andrew D. Lajium; Xavier Thayalan (DEStech Publications, 2015)
One form of online communication categorised as asynchronous is online discussion board forums. This paper presents the findings of a study on the interactive language functions and the phases of knowledge construction in asynchronous computer-mediated discourse (CMD) in an online discussion board forum in Malaysia. Data for the study was collected using purposive non-random data samples motivated by theme. It was found that the members of the online discussion forum used more assertive speech acts such as explaining, giving suggestions, agreeing, supporting, and answering to queries while interacting online. The second part of the study revealed that the most common phase of knowledge constructing was the act of sharing and comparing of opinion, as well as the discovery and exploration of dissonance or inconsistency among ideas, concepts or statements.